2013
DOI: 10.1016/j.nima.2013.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Bucking coil implementation on PMT for active canceling of magnetic field

Abstract: Aerogel and waterČerenkov detectors were employed to tag kaons for a Λ hypernuclear spectroscopic experiment which used the (e, e ′ K + ) reaction in experimental Hall C at Jefferson Lab (JLab E05-115). Fringe fields from the kaon spectrometer magnet yielded ∼ 5 Gauss at the photomultiplier tubes ( PMT ) for these detectors which could not be easily shielded. As this field results in a lowered kaon detection efficiency, we implemented a bucking coil on each photomultiplier tubes to actively cancel this magneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…We measured the magnetic field around positions where PMTs of the waterČerenkov detector will be, and found that there is about B y = 5 G at maximum *2 . In the study of [6], the gain of a PMT (Hamamatsu H7195), which is the similar PMT type to ours (Hamamatsu H11284-100UV), is reduced by 60% in the case that the magnetic field of B y = 5 G is yielded on the PMT. Therefore, the magnetic field on the PMTs should be suppressed in order to avoid a deterioration of the proton-rejection power which is caused by PMT-gain reductions.…”
Section: Figsupporting
confidence: 54%
See 3 more Smart Citations
“…We measured the magnetic field around positions where PMTs of the waterČerenkov detector will be, and found that there is about B y = 5 G at maximum *2 . In the study of [6], the gain of a PMT (Hamamatsu H7195), which is the similar PMT type to ours (Hamamatsu H11284-100UV), is reduced by 60% in the case that the magnetic field of B y = 5 G is yielded on the PMT. Therefore, the magnetic field on the PMTs should be suppressed in order to avoid a deterioration of the proton-rejection power which is caused by PMT-gain reductions.…”
Section: Figsupporting
confidence: 54%
“…Therefore, the magnetic field on the PMTs should be suppressed in order to avoid a deterioration of the proton-rejection power which is caused by PMT-gain reductions. For the waterČerenkov detector in S-2S, we plan to adopt the bucking coil method which was proven to work to recover the PMT gain against the similar strength of magnetic field (B y ≃ 4-6 G) in an experiment of Λ hypernuclear spectroscopy with the (e, e ′ K + ) reaction [6].…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the capability of on-line particle identification by theČerenkov detectors would be deteriorated. In order to ease the stray-magnetic field on PMTs, we are going to use both magneticfield shields and bucking coils [22]. We tested an implementation of the bucking coil on a PMT (Hamamatsu H11284-100UV [23]) which will be used for the waterČerenkov detector.…”
Section: Particle Detectorsmentioning
confidence: 99%